2012
DOI: 10.1007/978-1-4614-3055-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Testing of Nanomaterials

Abstract: The large-scale production and consumer exposure to a variety of nanotechnology innovations has stirred interest concerning the health consequences of human exposure to nanomaterials. In order to investigate these questions, in vitro systems are used to rapidly and inexpensively predict the effects of nanomaterials at the cellular level. Recent advances in the toxicity testing of nanomaterials are beginning to shed light on the characteristics, uptake and mechanisms of their toxicity in a variety of cell types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 76 publications
2
48
0
Order By: Relevance
“…Given the ever increasing use of NP in technological applications and everyday consumer goods and the high interest of exploiting the exceptional features of the NP in biomedical applications, it is expected that both intentional and unintentional exposure will become more frequent 4,5 . Because of this, the increase in nanotechnology implementation in our daily lives is joined with the raising of concerns on potential adverse effects towards human health 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the ever increasing use of NP in technological applications and everyday consumer goods and the high interest of exploiting the exceptional features of the NP in biomedical applications, it is expected that both intentional and unintentional exposure will become more frequent 4,5 . Because of this, the increase in nanotechnology implementation in our daily lives is joined with the raising of concerns on potential adverse effects towards human health 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, the increase in nanotechnology implementation in our daily lives is joined with the raising of concerns on potential adverse effects towards human health 6 . It is therefore recommended that the safety of these products, towards consumers and especially towards workers at the production site, is carefully evaluated before its introduction to the market 4,5,7 . However, there are currently only very limited regulations on the use and the safety criteria for nanomaterials in industrial applications or consumer goods.…”
Section: Introductionmentioning
confidence: 99%
“…The term ENM broadly encompasses a number of nano-sized materials that vary in shape, such as nanotubes, nanowires, or nanoparticles (NPs), which are generally defined as "any material having at least one dimension smaller than 100 nm." 1 Because of their extremely small size and high surface area, NPs offer a number of advantages over traditional "bulk" materials and are suitable for a wide variety of applications in consumer goods, 2,3 medical devices and diagnostics, [4][5][6] pharmaceutical products, 4,7-10 fuel additives, 11,12 and other industrial uses. [13][14][15][16][17] As a result, the number of manufactured goods containing NPs is continually rising; in 2006, manufacturers reported that NPs were incorporated in over 600 consumer products worth $50 billion in market value, 18 a number which has doubled to .1,600 NP-containing consumer products in 2013.…”
mentioning
confidence: 99%
“…Primary effects resulting from direct cellular NP contact may include toxicity, oxidative stress, DNA damage, and inflammation. 1,28,29 Because of their small size, NPs may translocate through tissue barriers into the blood, where they can circulate and eventually deposit in other organs, thereby generating a secondary NP exposure. Secondary effects may include toxicity at the site of NP deposition, in organs such as the liver, spleen, or kidneys, stimulation of systemic inflammation or alterations in systemic function.…”
mentioning
confidence: 99%
See 1 more Smart Citation